The role of the bank lending channel and impacts of stricter capital requirements on the Chinese banking industry - Qiyue Xiong (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
This paper focuses on the role the bank lending channel in transmission of monetary policy in China. Using unbalanced quarterly panel data from 2Q2000 to 4Q2011, a one-step GMM estimator is applied to establish the existence the bank lending channel. The findings suggest central bank monetary policy asymmetrically affects bank lending behavior. Small banks are found more sensitive to contractionary monetary policy in the Chinese context. Well capitalized banks appear to be more likely to adjust their lending behaviors in response to expansionary monetary policy, and conversely, undercapitalized banks tend to adjust with the advent of contractionary monetary policy. The importance of the bank lending channel declines after China introduced stricter capital regulations in early 2004, but the effect is still apparent in times of expansionary policy.
URN:NBN:fi:bof-201408072174
Keywords: Q20; Q20; E52; 330; bank characteristics; capital regulation; bank lending channel; asymmetric effects